A template-directed bifunctional NiSx/nitrogen-doped mesoporous carbon electrocatalyst for rechargeable Zn–air batteries. Issue 34 (14th August 2019) - Wan, Kai; Luo, Jiangshui; Zhang, Xuan; Zhou, Chen; Seo, Jin Won; Subramanian, Palaniappan; Yan, Jia-wei; Fransaer, Jan
Abstract : A highly ordered mesoporous NiS x /nitrogen-doped mesoporous carbon (NiS x /NMC) nanohybrid as a bifunctional oxygen electrocatalyst for rechargeable Zn–air batteries. Abstract : A highly ordered mesoporous nickel sulfides/nitrogen-doped mesoporous carbon (NiS x /NMC, wherein NiS x represents the combination of NiS and Ni3 S4, where 1 < x < 4/3) nanohybrid was synthesized by the assistance of a NMC template as an advanced bifunctional electrocatalyst for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). The use of NMC as a template improves the electronic conductivity of the catalyst, while the high specific surface area increases the number of active sites and the highly ordered mesoporous structure enables fast mass transfer. As a result, the Ni3 S4 /NMC catalyst shows a half-wave potential ( E 1/2 ) of 0.89 V vs. RHE for the ORR in 0.1 M KOH and a potential of 1.57 V vs. RHE at 10 mA cm −2 ( E j =10 ) for the OER in 1.0 M KOH. The potential gap Δ E (Δ E = E j =10 − E 1/2 ) is 0.68 V, which is significantly lower than the 0.8 V for 10 wt% Pt/C + IrO2 . The primary Zn–air battery shows a maximum power density of 186 mW cm −2 and an energy density as high as 805 W h kg −1 at 100 mA cm −2 . The battery also exhibits favorable long-term cycling behaviour (the polarization voltage increased by only 0.05 V after 300 charge/discharge cycles for 100 h). This work provides an effective strategy for the design of metal–carbon nanohybrid electrocatalysts for low-cost energy storage and conversion devices.